Implementation Decision Tree Algorithm for Ecommerce Website - Parlindungan,; HariSupriadi, (International Journal of Psychosocial Rehabilitation, 2020)
Making e-commerce websites has been widely used in business fields where buyers and sellers don't meet directly; the activities of transactions between one company or individually. The advantages of e-commerce marketing are that the products sold will be more numerous and varied and have a wide range too; shop owners do not need to open another branch to distribute goods. This e-commerce sales system will reduce operational costs because there is no need to use too many employees.The problem today is that on e-commerce websites there will be a very large number of transactions, which are caused by sales data and orders that are opened at any time and not limited by distance and time. This automatically means the amount of data ordering goods must be checked manually. The shop owner will sort and see the product and the number of orders; this is very difficult because of the category of goods sold when they are varied and consist of several product categories. The solution to the above problems can be overcome by adding a product category tracking system feature to the e-commerce website database. By adding the dec-tree algorithm concept, this algorithm will automatically record and read the number of transactions and the number of items sold. The system will then provide a report on the system of the best-selling number of goods and the amount of stock. The results of this report can be used to display a product that is most sold to be offered back to consumers or as a recommendation for the next stock procurement.